Serratiopeptidase a Hope in a Rapid and Better Improvement of Inflammatory Acne Vulgaris - M. Mikhael, Ehab; Y. Mohammed, Mahdi (Iraqi Journal of Pharmaceutical Sciences, 2017)
Acne vulgaris is a very common, chronic disorder, involving inflammation of the pilosebaceous units that can be varied in presentation and difficult to treat. Inflammatory acne may yield both scarring and pigmentary changes so early and adequate therapy will, in all cases, decrease its severity and may entirely suppress this disease. Serratiopeptidase has anti-inflammatory, anti-edemic and fibrinolytic activity and acts rapidly on localized inflammation. Serratiopeptidase was added in aim to hasten acne resolution. During March to July 2010, A comparative study for a 50 healthy patient suffering from acne was divided into 2 groups: 1st group treated by common acne modalities and the 2nd one with same modalities plus serratiopeptidase. All patients were followed up in out patient clinic by a dermatologist after 1st week of treatment and once weekly through the period of treatment. The results of this study showed that the effect of serratiopeptidase as adjuvant therapy for acne treatment result in a significant rapid improvement, this might be explained by serratiopeptidase ability in enhancing antibiotic efficacy and also increase the possibility of excellent improvement in acne appearance which may be due of it’s anti-inflammatory, anti-edemic. Serratiopeptidase was found to create a good hope as additional therapy for complicated acne vulgaris and bring a rapid and better improvement in treating acne.Key words: Acne ,Serratiopeptidase.